CAUSES OF THE GROWTH OF PUBLIC DEBT AND BUDGET DEFICIT IN ALBANIA: REPORT BASED ON RAPORT RULE OF MAASTRICHT (60/3 OF GNP) - RECOMMENDATIONS FOR REDUCING THESE PARAMETERS - Murrja, Arif; Ndregjoni, Agim; Cerpja, Teuta (European Scientific Journal, ESJ, 2014)
After the 2008 financial crisis in the U.S. and its transformation in the global economic crisis, the reduction of public debt and budget deficit have been key words in the design of public budget in each country. In this article, we analyze the causes of the growth of public debt over the limit (40-50% of GNP) of Albania as a developing country. However, two major causes of increasing public debt and budget deficit are (a) the current economic crisis and (b) the reduction of tax under the flat tax. The public debt and the budget deficit of Albania are increased over the limit defined in the rule report 60/30 Maastricht Treaty, mainly due to the deepening of the crisis and inefficiencies of the flat tax in public income collection. To argue that the economic crisis and tax reduction policies have led to increased public debt and budget deficit, we analyzed data on the budget deficit, public debt, remittances etc., for the period of 2000-2011. Another purpose of this paper is to compare the region with Albania, such as Bosnia- Herzegovina, Greece, Kosovo, Croatia, Montenegro, Macedonia, Romania, Serbia and Turkey.